The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s42003-021-01948-y
|View full text |Cite|
|
Sign up to set email alerts
|

High biodiversity in a benzene-degrading nitrate-reducing culture is sustained by a few primary consumers

Abstract: A key question in microbial ecology is what the driving forces behind the persistence of large biodiversity in natural environments are. We studied a microbial community with more than 100 different types of species which evolved in a 15-years old bioreactor with benzene as the main carbon and energy source and nitrate as the electron acceptor. Using genome-centric metagenomics plus metatranscriptomics, we demonstrate that most of the community members likely feed on metabolic left-overs or on necromass while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 87 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…Microbial community analyses indicated that a distinct member of the Peptococcaceae was growing while oxidizing benzene and other members of the community became also slightly enriched suggesting that benzene was mineralized by syntrophic interactions of the primary benzene degrader with nitrate reducers. Similar communities have been reported by others (Atashgahi et al, 2018; Kunapuli et al, 2007; Luo et al, 2016; Melkonian et al, 2021), but the initial degrader observed in this study is phylogenetically distinct from other putative benzene degraders indicating a broad diversity of anaerobic benzene degraders within the Peptococcaceae . In addition, benzene was likely initially carboxylated as indicated by metaproteomic detection of subunit AbcA of the putative benzene carboxlyase; this protein has always been detected in benzene‐degrading Peptococcaceae ‐dominated cultures to date.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Microbial community analyses indicated that a distinct member of the Peptococcaceae was growing while oxidizing benzene and other members of the community became also slightly enriched suggesting that benzene was mineralized by syntrophic interactions of the primary benzene degrader with nitrate reducers. Similar communities have been reported by others (Atashgahi et al, 2018; Kunapuli et al, 2007; Luo et al, 2016; Melkonian et al, 2021), but the initial degrader observed in this study is phylogenetically distinct from other putative benzene degraders indicating a broad diversity of anaerobic benzene degraders within the Peptococcaceae . In addition, benzene was likely initially carboxylated as indicated by metaproteomic detection of subunit AbcA of the putative benzene carboxlyase; this protein has always been detected in benzene‐degrading Peptococcaceae ‐dominated cultures to date.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we detected a UbiX‐like carboxylase 64.4% similar to a putative UbiX‐like carboxylase in the same benzene‐degrading culture BF (Table 2). The involvement of abc genes related to Peptococcaceae in benzene carboxylation under nitrate‐reducing conditions was reported in recent studies (Atashgahi et al, 2018; Luo et al, 2014; Melkonian et al, 2021; Toth et al, 2021); hence the results of these studies together with our data strongly suggest that carboxylation by Peptococcaceae is a common activation mechanism for benzene degradation under nitrate‐reducing conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Samples were centrifuged at 7600 relative centrifugal force at 10 °C for 5 min, and the supernatant was collected and filtered through a 0.22 µm-pore filter. Metabolite analysis by LC-MS was carried out as described in Melkonian et al (2021) with slight modifications. Five microliters of root extract was injected in a Nexera ultra-high performance liquid chromatography (UHPLC) system (Shimadzu, Den Bosch, The Netherlands) coupled to a high-resolution quadrupole time-of-flight mass spectrometer (Q-TOF; maXis 4G, Bruker Daltonics, Bruynvisweg 16/18).…”
Section: Methodsmentioning
confidence: 99%
“…Nealsonbacteria (OD1) and Ca . Omnitrophica (OP3), among others, are periodically observed in high abundances in the DGG-B/OR consortium (Luo et al, 2016; Toth et al, 2021) and other anaerobic benzene-degrading consortia (Taubert et al, 2012; Melkonian et al, 2021). What factors could explain such relatively high decay rates?…”
Section: Resultsmentioning
confidence: 99%